Third Meeting of DRDO Library Information Officers - DESIDOC, Director (DESIDOC Journal of Library & Information Technology, 2012)
The Third Meeting of Officers-in-Charge of Libraries and Technical Information Centres of DRDO Labs/Estts was held in DESIDOC on 5-6 November 1981 to take stock of the progress made.in the implementation of the recommendations made at the earlier to discuss further steps to be taken for providing better services to the scientists of DRDO. The Meeting was inaugurated by Prof M Krishnamurthi, CC R&D. 47 office rs all librari es/TICs attended the meeting. Dr AK Sreedhar, Director DSC; Dr I J Kumar, Director SAG; and Capt J J Baxi, Director WESO also attended the inaugural session. The Meeting covered the following four technical sessions : (a) Resource sharing in DROO Libraries/TICs (b) Augmentation of information services and manpower aspects (c) Admin procedures for Libraries/TICs (d) Information network for DRDO.